Pengaruh Tindakan Histerektomi terhadap Kualitas Kepuasan Seksual pada Pasien Plasenta Akreta di Indonesia (Literature review) - Ardelia Bertha Prastika; Intan Anggraini Arta Ningrum; Winda Aenah; Pungky Mulawardana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Placenta accreta is a complication in pregnancy that can increase the risk of maternal morbidity and mortality. Placenta accreta is a condition in which the implanted placental villi go too deep into the uterine wall. In the past few decades, the prevalence of placental cases in Indonesia has increased along with the increase in cesarean deliveries. Patients with post-hysterectomy can have changes in self-image acceptance that can affect psychological conditions and sexual satisfaction to post-traumatic stress disorder (PTSD). This study aims to determine how the effect of hysterectomy on the level of sexual satisfaction in placenta accreta patients in Indonesia. This study used a literature review study design. Research article searches were sourced from the PubMed, Google Scholar, and SCOPUS electronic databases. Search articles using keywords, namely hysterectomy, placenta accreta, sexual satisfaction. The results of a review of three journals that have been carried out show that the incidence of placenta accreta in placenta previa is quite worrying, namely as much as 25-50% and is a priority for cesarean section. The treatment that is often the choice is hysterectomy. The results showed that the effects of hysterectomy on women included orgasm problems, decreased libido, accelerated menopause, and nerve damage. This causes 10-20% of women to experience a decline in sexual function. The data that we reviewed can be concluded that although there are sexual dysfunction disorders in placenta accreta patients with hysterectomy therapy, there is no significant difference in the level of sexual desire between patients with hysterectomy and without hysterectomy in cases of placenta accreta.